Sustainable Kapok Fiber-Derived Carbon Microtube as Broadband Microwave Absorbing Material - Long, Aichun; Zhao, Pengfei; Liao, Lusheng; Wang, Rui; Tao, Jinlong; Liao, Jianhe; Liao, Xiaoxue; Zhao, Yanfang (Materials, 2022)
The design of hierarchical structures from biomass has become one of the hottest subjects in the field of microwave absorption due to its low cost, vast availability and sustainability. A kapok-fiber-derived carbon microtube was prepared by facile carbonization, and the relation between the structure and properties of the carbonized kapok fiber (CKF) was systematically investigated. The hollow tubular structures afford the resulting CKF composites with excellent microwave-absorbing performance. The sample with a 30 wt.% loading of CKF in paraffin demonstrates the strongest microwave attenuation capacity, with a minimum reflection loss of −49.46 dB at 16.48 GHz and 2.3 mm, and an optimized effective absorption bandwidth of 7.12 GHz (10.64–17.76 GHz, 2.3 mm) that covers 34% of the X-band and 96% of the Ku-band. Further, more than 90% of the incident electromagnetic wave in the frequency from 4.48 GHz to 18.00 GHz can be attenuated via tuning the thickness of the CKF-based absorber. This study outlines a foundation for the development of lightweight and sustainable microwave absorbers with a high absorption capacity and broad effective absorption bandwidth.